2018
DOI: 10.1007/s10911-018-9393-3
|View full text |Cite
|
Sign up to set email alerts
|

Moderate High Temperature Condition Induces the Lactation Capacity of Mammary Epithelial Cells Through Control of STAT3 and STAT5 Signaling

Abstract: In lactating mammary glands, alveolar mammary epithelial cells (MECs) synthesize and secrete milk components. MECs also form less permeable tight junctions (TJs) to prevent the leakage of milk components. During lactation, MECs are exposed to temperature changes by metabolic heat production and air ambient temperature. In this study, we investigated whether temperature changes influence milk production ability and TJ barriers in MECs by using two lactating culture models. The results showed that 39 °C treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…A lactating MEC culture model was prepared as previously reported. [ 27 ] Intracellular and secreted β‐caseins were detected in the MEC layer and the culture medium, respectively, by western blotting ( Figure 2 A). MECs treated with 0.033% PMO showed significant decreases in both intracellular and secreted β‐caseins (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lactating MEC culture model was prepared as previously reported. [ 27 ] Intracellular and secreted β‐caseins were detected in the MEC layer and the culture medium, respectively, by western blotting ( Figure 2 A). MECs treated with 0.033% PMO showed significant decreases in both intracellular and secreted β‐caseins (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…A culture model of lactating MECs was prepared as previously reported. [ 27 ] Briefly, MECs were isolated from the mammary glands of virgin mice by collagenase treatment and the low spin centrifugation in 50% fetal bovine serum (Thermo Fisher Scientific). MECs were cultured in RPMI‐1640 supplemented with 10% fetal bovine serum (GIBCO‐BRL, Grand Island, NY), 10 μg mL −1 insulin (Sigma‐Aldrich), 10 ng mL −1 epidermal growth factor (BD Biosciences, San Diego, CA), 100 U/mL penicillin (GIBCO‐BRL, Grand Island, NY), and 100 μg mL −1 streptomycin (GIBCO) at 37 °C on a cell culture insert in a 24‐well plate (0.4‐μm pore size; Falcon, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Mild heat stress (39 • C-40 • C) can positively regulate cell proliferation and differentiation [6]. Indeed, a previous study has shown that heat-shock at 39 • C has activated milk production and enhanced the formation of less-permeable TJs [7,8]. However, detailed molecular mechanisms of the mammary epithelial cell response to mild heat shock have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the expression of milk protein β‐casein is increased by mild heat treatment at 39°C in mammary epithelial cells (Kobayashi et al, ), although the detailed mechanism is unknown. Our previous studies suggested that UPR factors, XBP1 and ATF4, regulate the differentiation of mammary epithelial cells by controlling the expression of lactogenic hormones (Tsuchiya et al, ; Yonekura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secretory epithelial cells, including sweat glands and salivary glands, have been found to exhibit temperature-dependent changes (DiPasquale, Buono, & Kolkhorst, 2003;Elishoov, Wolff, Kravel, Shiperman, & Gorsky, 2008). In mammary epithelial cells, the expression of β-casein, a representative milk protein, increases under mild heat stress (39°C) (Kobayashi, Tsugami, Matsunaga, Suzuki, & Nishimura, 2018). These findings suggest that the physiological functions of mammary epithelial cells may change with temperature.…”
mentioning
confidence: 99%